An Analysis Of The Performance Of Autonomous Navigation On An Ardupilot-Controlled Rover - Adik Susilo Wardoyo; Indri Purwita Sary; Ilham Taufik Maulana (Faculty of Engineering and Informatics, Universitas Multimedia Nusantara, 2022)
Monitoring forests is one of the strategies in the overall preventive strategy. Monitoring the forest can quickly and permanently manage how tree illnesses emerge, spread, and evolve. To help monitor forest fires, a robot platform that can operate independently and assist in data collection can be created. In this paper, the accuracy of the Ardupilot-controlled autonomous navigation system of the rover was examined. The metode are used is experimental study, the study consists of a comparison between the GPS rover log and the SITL simulation within the mission planner tool. The average accuracy achieved by altering the route's distance and shape is 94.58%. The lengthy path may be the source of the rover's inaccurate autonomous navigation. In this case, the turning angle problem has no real effect on how well and accurately the rover navigates on its own.